Interaction processes at the concrete-bentonite interface after 13 years of FEBEX-Plug operation. Part II: Bentonite contact. (June 2017) - Fernández, Raúl; Torres, Elena; Ruiz, Ana I.; Cuevas, Jaime; Alonso, María Cruz; García Calvo, José Luis; Rodríguez, Enrique; Turrero, María Jesús
Abstract: The in situ FEBEX experiment performed at the URL in Grimsel (Swizerland) was dismantled after 18 years of operation. Interface samples between bentonite and a shotcreted concrete plug that was constructed in a second operational phase have been studied after 13 years of interaction. Mineralogical and geochemical characterization of samples have been performed by XRD, SEM-EDX, TG and FTIR techniques in addition to determinations of major ions by chemical analysis of aqueous extracts, δ 18 O and δ 13 C stable isotopes both in concrete paste and bentonite, and exchangeable cations in bentonite. Low mineralogical alteration impact was observed in bentonite that is only affected by a few millimeters. A large accumulation of Mg was observed at the bentonite side of the interface precipitating as silicates in various forms. In addition, heterogeneous carbonation was observed at the interface, but mostly affecting the concrete side. Migration of aqueous species occurred, being the most relevant the diffusion of chloride and sulfate from bentonite to concrete, in agreement with Part I of this study. Chloride advanced more into the concrete, while sulfates reacted to form ettringite, which has an evident alteration impact at the very interface (<0.5 mm rim) within the concrete. The ionic mobility has also redistributed the exchangeable cations in bentonite, increasing the content in Ca 2+ and Na +, compensated by a decrease in Mg 2+ . The results presented in this paper complement those presented in Part I, focusing on the alteration of concrete by the bentonite and the granite groundwater. Highlights: Bentonite-concrete interface has been examined after 13 years of interaction at the GTS. A carbonated rim and ettringite precipitation occur in concrete near the interface. Ca and Al accumulate in concrete and are depleted at the interface of bentonite. Exchangeable Mg is released from bentonite and precipitates as trioctahedral Mg silicate. Low bentonite alteration and high concrete reactivity is observed overall.